Breathable water-based microfiber leather and its manufacturing process

By adjusting the slurry formula and process flow, a breathable water-based ultra-fiber leather was prepared, which solved the problem of damage to the breathability and softness of the existing water-based ultra-fiber leather during hot water fibre opening, and achieved high breathability and Softness product.

CN119061699BActive Publication Date: 2025-02-25FUJIAN JILI NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411549144.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-25
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The existing water-based ultra-fiber leather is prone to damage to the microporous breathable structure due to hydrophilic swelling during hot water fiber opening, which affects its breathability and softness.

Method used

By adjusting the slurry formula and process flow, it includes preparing multi-layer base cloth, immersing the first aqueous PU slurry and first curing, acid hydrolysis and water washing, immersing the second aqueous PU slurry and second curing, hot water opening For fiber and drying, zinc ammonia complex and water-soluble powder are used to form a through microporous structure and compensate for the internal microporous structure, inhibit the detachment of hydrophilic groups, and maintain breathability and softness.

Benefits of technology

The air permeability and softness of the ultra-fiber leather are improved, and the damage to the microporous structure during hot water fiber production is avoided, ensuring the excellent performance of the product.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of ultra-fine leather, and specifically to a breathable water-based ultra-fine leather and a manufacturing process thereof, comprising the following steps: S1, preparing a multi-layer base fabric; S2, impregnating a first water-based PU slurry and curing for the first time; S3, acid hydrolysis and water washing; S4, impregnating a second water-based PU slurry and curing for the second time; S5, hot water fiber opening and drying. The present invention introduces zinc-ammonium complexes into the slurry, and thermally decomposes them in the curing stage to generate zinc ions and ammonia gas that can demulsify and coagulate the polyurethane, and the ammonia gas escapes to form a through microporous structure, and the water-soluble powder dissolves into pores in the hot water fiber opening, which is beneficial to compensate for the microporous structure inside the second water-based polyurethane resin layer, and the acid solution is soaked to hydrolyze the sulfonylurea and remove the hydrophilic group of the first water-based polyurethane resin layer, thereby suppressing the degree of damage to the microporous breathable structure caused by hydrophilic swelling during the hot water fiber opening process and the degree of damage to the release structure on the surface of the ultra-fine fiber, thereby obtaining a breathable and soft ultra-fine leather.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ultra-fine leather, and in particular to a breathable water-based ultra-fine leather and a manufacturing process thereof. Background Art

[0002] The currently produced microfiber-based fabrics are divided into water-based microfiber-based fabrics and solvent-based microfiber-based fabrics. Compared with solvent-based microfiber-based fabrics, the preparation method of water-based microfiber-based fabrics is more environmentally friendly, and water is used instead of organic solvents, which greatly saves costs.

[0003] At present, most synthetic leathers on the market use solvent-based polyurethane, which has poor environmental protection and a large amount of organic solvent volatilization during the production process, which does not conform to the current trend of green environmental protection. Since water-based polyurethane uses water as a dispersion medium, there is no solvent volatilization during the production process, which does not pollute the environment and does not harm the health of operators in the production workshop. It is more environmentally friendly and harmless, and water-based polyurethane is increasingly used in the field of synthetic leather.

[0004] With the advancement of technology, water-soluble sea-island fibers with polyvinyl alcohol as the sea phase have appeared on the market. They can be used as non-woven fabrics and can be opened by hot water. However, in order to increase the affinity with water, water-based polyurethane introduces a large number of hydrophilic groups into the molecular chain. These hydrophilic groups make the impregnated leather easy to swell due to hydrophilicity during the hot water opening process. During the hot water opening process, the sea phase in the sea-island fiber is continuously extracted to leave pores. Under the action of the mechanical force of the roller and the heat of the solvent, the water-based polyurethane resin continuously fills the pores and adheres to the surface of the ultrafine fiber, causing the release structure between the ultrafine fiber and the polyurethane resin to be eventually destroyed, and it becomes more compacted after the reduction is completed; at the same time, the microporous structure formed by the water-based polyurethane during the curing stage is also easily squeezed by the water-based polyurethane resin during the expansion process, which affects the air permeability of the ultrafine leather. Summary of the invention

[0005] The purpose of the invention is to provide a breathable water-based microfiber leather and a production process thereof, and to collaboratively ensure the softness and breathability of the microfiber leather through the adjustment of the slurry formula and the improvement of the process.

[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:

[0007] The production process of breathable water-based microfiber leather specifically includes the following steps:

[0008] S1. Preparing a multi-layer base fabric: taking a waterborne polyurethane mesh as an elastic middle layer and a sea-island fiber nonwoven fabric as an upper and lower interlayer, and compounding the three layers and needle-punching to form a multi-layer base fabric;

[0009] S2, impregnation with first aqueous PU slurry and first curing: immersing the multi-layer base fabric of step S1 in the first aqueous PU slurry, wherein the first aqueous PU slurry comprises the first aqueous polyurethane, zinc-amine complex, defoamer, leveling agent, thickener and deionized water, and has a solid content of 15%-25%, a room temperature viscosity of 800mPa·s-1500mPa·s, and a liquid carrying rate of 100%-130%; after the first curing, the impregnated bass semi-finished product A is obtained;

[0010] S3, acid hydrolysis and water washing: soak the semi-finished product A containing bess in step S2 in acid solution to hydrolyze and remove the hydrophilic group, the pH value is controlled at 4.0-4.5, the hydrolysis temperature is 45°C-55°C, and the hydrolysis time is 40min-60min to obtain the hydrolyzed bess semi-finished product;

[0011] S4, impregnation with second aqueous PU slurry and second curing: immerse the hydrolyzed bass semi-finished product of step S3 into the second aqueous PU slurry, wherein the components of the second aqueous PU slurry are second aqueous polyurethane, water-soluble powder, zinc ammine complex, defoamer, leveling agent, thickener and deionized water, with a solid content of 25%-40%, a room temperature viscosity of 2000mPa•s~2500mPa•s, and a liquid rate of 200%-300%; after the second curing, the impregnated bass semi-finished product B is obtained;

[0012] S5, hot water fiber opening and drying: the semi-finished product B impregnated with bass in step S4 is subjected to a fiber opening treatment by reducing weight in hot water at 75°C-95°C, and then dried to obtain water-based microfiber leather.

[0013] Preferably, the fineness of the sea-island fibers in step S1 is 1.5 dtex to 6.5 dtex, and the number of islands is 37.

[0014] Preferably, the sea component of the sea-island fibers in step S1 is water-soluble polyester WSPET, and the island component is PET.

[0015] Preferably, the acupuncture density in step S1 is 600 to 800 punctures / cm 2 , the weight of the multi-layer base fabric is 250g / m 2 ~450g / m 2 .

[0016] Preferably, the water-soluble powders in the second aqueous PU slurry are all water-soluble acrylic acid oligomers with a polymerization rate of 95%.

[0017] Preferably, the first curing in step S2 and the second curing in step S4 both adopt a two-stage drying method, first directly heating at a temperature of 85°C-95°C for 3min-5min, and then completely drying at a temperature of 110°C-120°C.

[0018] Preferably, the hard segment diisocyanate of the first aqueous polyurethane in step S2 is hexamethylene diisocyanate or isophorone diisocyanate, the soft segment is a small molecule diol and polytetrahydrofuran or polycarbonate diol, and the hydrophilic chain extender is p-sulfamoylbenzoic acid and is located at the end of the molecular chain.

[0019] Preferably, the hard segment diisocyanate of the second aqueous polyurethane in step S4 is hexamethylene diisocyanate or isophorone diisocyanate, the soft segment is a small molecule diol and polytetrahydrofuran or polycarbonate diol, and the hydrophilic chain extender is dimethylol propionic acid.

[0020] Preferably, the reduction fiber opening treatment of step S5 is specifically as follows: the semi-finished product B containing bass in step S4 is sequentially immersed in different fiber opening grooves with increasing temperatures for hot water fiber opening, the water temperature increment is 5°C-10°C, the treatment time of each fiber opening groove is 10min±3min, and the outlet of each fiber opening groove is subjected to immersion treatment, and the pressure is 6kg / cm 2 ~8kg / cm 2 .

[0021] The present invention also provides a breathable water-based ultra-fine leather produced by the production process.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The manufacturing process of the present invention comprises the following steps: impregnating a first aqueous PU slurry on a multi-layer base fabric, acid hydrolyzing and impregnating a second aqueous PU slurry, introducing a zinc-ammonium complex into both the first aqueous PU slurry and the second aqueous PU slurry, thermally decomposing them in a curing stage to generate zinc ions and ammonia gas that can demulsify and coagulate the polyurethane, the ammonia gas escapes to form a through microporous structure, and the water-soluble powder in the second aqueous polyurethane resin layer formed by the second curing is dissolved into pores in hot water fiber opening, which is beneficial to compensate for the microporous structure inside the second aqueous polyurethane resin layer. In addition, the first aqueous polyurethane resin layer formed after the first curing is soaked in acid solution so that the sulfonylurea is hydrolyzed to remove the hydrophilic groups of the first aqueous polyurethane resin layer, thereby suppressing the damage degree of the microporous air-permeable structure caused by the hydrophilic swelling of the aqueous polyurethane in the hot water fiber opening process and the damage degree of the release structure on the surface of the ultrafine fiber, thereby obtaining a breathable and soft ultrafine leather. DETAILED DESCRIPTION Example 1

[0024] The present embodiment provides a breathable water-based microfiber leather, and its production process specifically includes the following steps: S1, preparing a multi-layer base fabric; S2, impregnating with a first water-based PU slurry and performing a first curing; S3, acid hydrolysis and water washing; S4, impregnating with a second water-based PU slurry and performing a second curing; S5, hot water fiber opening and drying.

[0025] In step S1, a waterborne polyurethane mesh is used as an elastic middle layer and a sea-island fiber nonwoven fabric is used as an upper and lower interlayer. The three layers are compounded and needle-punched to form a multi-layer base fabric. The needle-punching density is 650 thorns / cm 2 , the weight of the multi-layer base fabric is 300g / m 2 The fineness of the sea-island fiber is 5 dtex, the number of islands is 37, the sea component is water-soluble polyester WSPET, and the island component is PET.

[0026] In step S2, the multi-layer base fabric of step S1 is immersed in the first aqueous PU slurry with a liquid rate of 120%, and the impregnated base semi-finished product A is obtained after the first curing; the components of the first aqueous PU slurry are the first aqueous polyurethane, zinc ammine complex, BYK1790 defoamer, leveling agent, DH-72165 thickener and deionized water, with a solid content of 20% and a room temperature viscosity of 1000mPa•s, which can make the impregnation liquid fully penetrate into the gaps between the fibers and improve the absorption rate of the non-woven fabric to the impregnation liquid.

[0027] In step S3, the impregnated bass semi-finished product A of step S2 is immersed in an acid solution to hydrolyze and remove the hydrophilic group, the pH value is controlled at 4.5, the hydrolysis temperature is 55°C, and the hydrolysis time is 50 minutes to obtain a hydrolyzed bass semi-finished product.

[0028] In step S4, the hydrolyzed Bes semi-finished product of step S3 is immersed in the second aqueous PU slurry, with a liquid rate of 250%, and the impregnated Bes semi-finished product B is obtained after the second curing. The components of the second aqueous PU slurry are the second aqueous polyurethane, water-soluble powder, zinc-ammine complex, BYK1790 defoamer, leveling agent, DH-72165 thickener and deionized water, with a solid content of 35% and a room temperature viscosity of 2500mPa•s. The water-soluble powders are all water-soluble acrylic oligomers with a polymerization rate of 95%. The water-soluble acrylic oligomers are obtained by copolymerizing acrylic acid, hydroxypropyl acrylate and N-hydroxymethyl acrylamide as monomers in an aqueous solution under the action of an initiator at a molar ratio of 5:4:1.

[0029] The hard segment diisocyanate of the first waterborne polyurethane in step S2 is isophorone diisocyanate, the soft segment is polycarbonate diol and small molecule diol, and the hydrophilic chain extender is p-sulfamoylbenzoic acid and is located at the end of the molecular chain. Its synthesis route is to first vacuum dehydrate the polycarbonate diol, then mix it with isophorone diisocyanate IPDI and stir it evenly under a nitrogen atmosphere, then add a catalyst to react until the polycarbonate diol is completely consumed and isophorone diisocyanate IPDI has a surplus, then cool down to adjust the viscosity, add a small molecule diol (1,4-butanediol) to continue the reaction until the NCO mass fraction reaches 4.5%, then add p-sulfamoylbenzoic acid to react completely, the end of the molecular chain is benzoic acid, cool down and add TEA for neutralization reaction, then add deionized water for emulsification and dispersion, and remove the organic solvent to obtain the first waterborne polyurethane.

[0030] The hard segment diisocyanate of the second waterborne polyurethane in step S4 is isophorone diisocyanate IPDI, the soft segment is polycarbonate diol and small molecule diol, and the hydrophilic chain extender is dimethylol propionic acid. The synthesis route is to first vacuum dehydrate the polycarbonate diol, then mix it with isophorone diisocyanate IPDI and stir it evenly under a nitrogen atmosphere, then add a catalyst to react until the polycarbonate diol is completely consumed and isophorone diisocyanate IPDI has a surplus, then cool down to adjust the viscosity, add small molecule diol (1,4-butanediol) and dimethylol propionic acid, continue to react until the NCO mass fraction reaches 4.5%, cool down and add TEA for neutralization reaction, then add deionized water and EDA, emulsify and disperse, and remove the organic solvent to obtain the second waterborne polyurethane.

[0031] The first curing in step S2 and the second curing in step S4 both adopt a two-stage drying method, first directly heating at 95° C. for 3 minutes, and then completely drying at 120° C.

[0032] In step S5, the impregnated bass semi-finished product B of step S4 is subjected to a reduction fiber opening treatment in hot water, and then dried to obtain water-based microfiber leather. The reduction fiber opening treatment is specifically as follows: the impregnated bass semi-finished product B of step S4 is sequentially immersed in different fiber opening tanks with increasing temperatures for hot water fiber opening: the first fiber opening tank has a water temperature of 75°C and a treatment time of 10 minutes; the second fiber opening tank has a water temperature of 85°C and a treatment time of 10 minutes; the third fiber opening tank has a water temperature of 90°C and a treatment time of 10 minutes; the fourth fiber opening tank has a water temperature of 95°C and a treatment time of 10 minutes; and each fiber opening tank outlet is subjected to a rolling treatment, and the pressure is 8kg / cm 2 . Example 2

[0033] The present embodiment provides a breathable water-based microfiber leather, and its production process specifically includes the following steps: S1, preparing a multi-layer base fabric; S2, impregnating with a first water-based PU slurry and performing a first curing; S3, acid hydrolysis and water washing; S4, impregnating with a second water-based PU slurry and performing a second curing; S5, hot water fiber opening and drying.

[0034] In step S1, a waterborne polyurethane mesh is used as an elastic middle layer and a sea-island fiber nonwoven fabric is used as an upper and lower interlayer. The three layers are compounded and needle-punched to form a multi-layer base fabric. The needle-punching density is 800 punctures / cm 2 , the weight of the multi-layer base fabric is 350g / m 2 The fineness of the sea-island fiber is 5 dtex, the number of islands is 37, the sea component is water-soluble polyester WSPET, and the island component is PET.

[0035] In step S2, the multi-layer base fabric of step S1 is immersed in the first aqueous PU slurry with a liquid rate of 130%, and the impregnated base semi-finished product A is obtained after the first curing; the components of the first aqueous PU slurry are the first aqueous polyurethane, zinc ammine complex, BYK1790 defoamer, leveling agent, DH-72165 thickener and deionized water, with a solid content of 20% and a room temperature viscosity of 1000mPa•s, which can make the impregnation liquid fully penetrate into the gaps between the fibers and improve the absorption rate of the non-woven fabric to the impregnation liquid.

[0036] In step S3, the impregnated bass semi-finished product A of step S2 is immersed in an acid solution to hydrolyze and remove the hydrophilic group, the pH value is controlled at 4.0, the hydrolysis temperature is 45°C, and the hydrolysis time is 60 minutes to obtain a hydrolyzed bass semi-finished product.

[0037] In step S4, the hydrolyzed Bes semi-finished product of step S3 is immersed in the second aqueous PU slurry, with a liquid rate of 300%, and the impregnated Bes semi-finished product B is obtained after the second curing. The components of the second aqueous PU slurry are the second aqueous polyurethane, water-soluble powder, zinc-ammine complex, BYK1790 defoamer, leveling agent, DH-72165 thickener and deionized water, with a solid content of 35% and a room temperature viscosity of 2500mPa•s. The water-soluble powders are all water-soluble acrylic oligomers with a polymerization rate of 95%. The water-soluble acrylic oligomers are obtained by copolymerizing acrylic acid, hydroxypropyl acrylate and N-hydroxymethyl acrylamide as monomers in an aqueous solution under the action of an initiator at a molar ratio of 5:4:1.

[0038] The hard segment diisocyanate of the first waterborne polyurethane in step S2 is hexamethylene diisocyanate, the soft segment is polytetrahydrofuran and a small molecule diol, and the hydrophilic chain extender is p-sulfamoylbenzoic acid and is located at the end of the molecular chain. Its synthesis route is to first vacuum dehydrate polytetrahydrofuran, then mix it with hexamethylene diisocyanate HDI and stir it evenly under a nitrogen atmosphere, then add a catalyst to react until the polytetrahydrofuran is completely consumed and the hexamethylene diisocyanate HDI has a surplus, then cool down to adjust the viscosity, add a small molecule diol (1,4-butanediol) to continue the reaction until the NCO mass fraction reaches 4.5%, then add p-sulfamoylbenzoic acid to react completely, the end of the molecular chain is benzoic acid, cool down and add TEA for neutralization reaction, then add deionized water for emulsification and dispersion, and remove the organic solvent to obtain the first waterborne polyurethane.

[0039] The hard segment diisocyanate of the second waterborne polyurethane in step S4 is hexamethylene diisocyanate HDI or isophorone diisocyanate IPDI, the soft segment is a small molecule diol and polytetrahydrofuran, and the hydrophilic chain extender is dimethylol propionic acid. The synthesis route is to first vacuum dehydrate polytetrahydrofuran, then mix it with hexamethylene diisocyanate HDI and stir it evenly under a nitrogen atmosphere, then add a catalyst to react until the polytetrahydrofuran is completely consumed and there is a surplus of hexamethylene diisocyanate HDI, then cool down to adjust the viscosity, add a small molecule diol (1,4-butanediol) and dimethylol propionic acid, continue to react until the NCO mass fraction reaches 4.5%, cool down and add TEA for neutralization reaction, then add deionized water and EDA, emulsify and disperse, and remove the organic solvent to obtain the second waterborne polyurethane.

[0040] The first curing in step S2 and the second curing in step S4 both adopt a two-stage drying method, first directly heating at 95° C. for 5 minutes, and then completely drying at 115° C.

[0041] In step S5, the impregnated bass semi-finished product B of step S4 is subjected to a reduction fiber opening treatment in hot water, and then dried to obtain water-based microfiber leather. The reduction fiber opening treatment is specifically as follows: the impregnated bass semi-finished product B of step S4 is sequentially immersed in different fiber opening tanks with increasing temperatures for hot water fiber opening: the first fiber opening tank has a water temperature of 75°C and a treatment time of 10 minutes; the second fiber opening tank has a water temperature of 85°C and a treatment time of 10 minutes; the third fiber opening tank has a water temperature of 90°C and a treatment time of 10 minutes; the fourth fiber opening tank has a water temperature of 95°C and a treatment time of 10 minutes; and each fiber opening tank outlet is subjected to a rolling treatment, and the pressure is 7kg / cm 2 .

[0042] The softness of microfiber leather was measured by using GT-303 leather softness tester: the microfiber leather was cut into the required rectangular cloth sample, and then placed on the base of the instrument, and the pressing handle was first folded down to make the probe completely retracted, and the base cloth was clamped between the clamping bases, and the upper arm was locked. After releasing the hand, the pointer rotated, and after the pointer stabilized, the pointer reading was read. Among them: the softness of Examples 1 and 2 was 7.93 and 7.82 respectively.

[0043] The YG461H fully automatic air permeability instrument produced by Ningbo Textile Instrument Co., Ltd. was used to characterize the air permeability of microfiber leather. The test pressure was 125Pa and the test area was 20cm 2 , automatically adjust the size of the air nozzle. Among them: the air permeability of embodiments 1 and 2 is 74.8 mm / s and 72.6 mm / s respectively.

[0044] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which shall fall within the scope of the present invention to be protected. The scope of protection of the present invention shall be defined by the attached claims and their equivalents.

Claims

1. Breathable water-based microfiber leather production process, characterized in that: The specific steps include: S1. Prepare a multi-layer base fabric: take a water-based polyurethane mesh as an elastic middle layer and a sea-island fiber nonwoven fabric as an upper and lower interlayer, and compound the three layers and then needle-punch to form a multi-layer base fabric, wherein the sea component of the sea-island fiber is a water-soluble polyester WSPET, and the island component is PET; S2, impregnation with first aqueous PU slurry and first curing: immersing the multi-layer base fabric of step S1 in the first aqueous PU slurry, wherein the first aqueous PU slurry comprises the first aqueous polyurethane, zinc-amine complex, defoamer, leveling agent, thickener and deionized water, and has a solid content of 15%-25%, a room temperature viscosity of 800mPa·s-1500mPa·s, and a liquid carrying rate of 100%-130%; after the first curing, the impregnated bass semi-finished product A is obtained; The hard segment diisocyanate of the first waterborne polyurethane is hexamethylene diisocyanate or isophorone diisocyanate; the hydrophilic chain extender is p-sulfamoylbenzoic acid and is located at the end of the molecular chain; the soft segment is a small molecule diol and polytetrahydrofuran, or the soft segment is a small molecule diol and polycarbonate diol; S3, acid hydrolysis and water washing: soak the semi-finished product A containing bess in step S2 in acid solution to hydrolyze and remove the hydrophilic group, the pH value is controlled at 4.0-4.5, the hydrolysis temperature is 45°C-55°C, and the hydrolysis time is 40min-60min to obtain the hydrolyzed bess semi-finished product; S4, impregnation with second aqueous PU slurry and second curing: immerse the hydrolyzed bass semi-finished product of step S3 into the second aqueous PU slurry, wherein the components of the second aqueous PU slurry are second aqueous polyurethane, water-soluble powder, zinc ammine complex, defoamer, leveling agent, thickener and deionized water, with a solid content of 25%-40%, a room temperature viscosity of 2000mPa•s~2500mPa•s, and a liquid rate of 200%-300%; after the second curing, the impregnated bass semi-finished product B is obtained; S5, hot water fiber opening and drying: the semi-finished product B impregnated with bass in step S4 is subjected to a fiber opening treatment by reducing weight in hot water at 75°C-95°C, and then dried to obtain water-based microfiber leather.

2. The process for producing breathable water-based microfiber leather according to claim 1, characterized in that: The fineness of the sea-island fibers in step S1 is 1.5 dtex to 6.5 dtex, and the number of islands is 37.

3. The process for producing breathable water-based microfiber leather according to claim 1, characterized in that: The acupuncture density in step S1 is 600 to 800 punctures / cm 2 , the weight of the multi-layer base fabric is 250g / m 2 ~450g / m 2 .

4. The process for producing breathable water-based microfiber leather according to claim 1, characterized in that: The water-soluble powders in the second aqueous PU slurry are all water-soluble acrylic acid oligomers with a polymerization rate of 95%.

5. The process for producing breathable water-based microfiber leather according to claim 1, characterized in that: The first curing in step S2 and the second curing in step S4 both adopt a two-stage drying method, first directly heating at a temperature of 85° C.-95° C. for 3 min-5 min, and then completely drying at a temperature of 110° C.-120° C.

6. The process for producing breathable water-based microfiber leather according to claim 1, characterized in that: The hard segment diisocyanate of the second aqueous polyurethane in step S4 is hexamethylene diisocyanate or isophorone diisocyanate; the hydrophilic chain extender is dimethylol propionic acid; the soft segment is a small molecule diol and polytetrahydrofuran, or the soft segment is a small molecule diol and polycarbonate diol.

7. The process for producing breathable water-based microfiber leather according to claim 1, characterized in that: The decompression fiber opening treatment of step S5 is specifically as follows: the semi-finished product B containing the bass impregnated in step S4 is sequentially immersed in different fiber opening tanks with increasing temperatures for hot water fiber opening, the water temperature increment is 5°C-10°C, the treatment time of each fiber opening tank is 10min±3min, and the outlet of each fiber opening tank is subjected to a padding treatment, and the pressure is 6kg / cm 2 ~8kg / cm 2 .

8. A breathable water-based microfiber leather made by the manufacturing process as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Water-dilutable resin-based impregnation method for ultrafine fiber synthetic leather base fabrics

    CN104005237A

  • Preparation method of fully aqueous superfine fiber synthetic leather

    CN111764177A

  • Preparation method of waterborne polyurethane figured island fiber base

    CN115961480A